Children Acquiring a Second Language: Some Insights Gained from Talking to Six Urban Pre-School Malaysian Children - Yeoh, Audrey Ambrose (Journal of Modern Languages, 2017)
This study considers the different ways in which English has featured in the lives of urban Malaysian children throw some light on several factors or situations which exist in urban Malaysia. The paper reveals that most pre-school urban children are already able to handle a second language besides their mother tongue before they begin formal language lessons at school.